Development e-Module (E-Lapen) based Augmented Reality to Increase Students' Interest in Learning - Hernandha Putri, Annisa; Fakhriyah, Fina; Amaliyah, Fitriyah (CV. Creative Tugu Pena, 2024)
This research aims to give test the effectiveness of interactive media in development E-LAPEN based Augmented Reality in increasing students' interest in learning. This research uses Research and Development (Rnd) with the ADDIE development model. The instruments used in this research were interest in learning questionnaires andpre-test as well as post-test. The results of the validation carried out by material and media experts respectively show that the criteria are very feasible, with respective scores of 95% for material and 90% for media. After implementing the media, a questionnaire regarding interest in learning was given before and after using the mediapre-test andpost-test. The results of this study show that there is an improvement before and after useE-module This is a percentage that previously had 57% of all questions showing high and quite high interest and interest in learning, but after using the module, this percentage increased to 98% and was supported by an increase in scores.pre-test andpost-test amounting to 20.98%. So, it can be concluded that the useE-Module basedAugmented Reality effective for increasing students' interest in learning. Keywords: Augmented Reality, Development e-Module, E-Lapen